2016
DOI: 10.1038/srep37558
|View full text |Cite
|
Sign up to set email alerts
|

Combinational Immunotherapy with Allo-DRibble Vaccines and Anti-OX40 Co-Stimulation Leads to Generation of Cross-Reactive Effector T Cells and Tumor Regression

Abstract: It is well-known that vaccines comprising of irradiated whole tumor cells or tumor-derived heat shock proteins can generate tumor-specific immune responses. In contrast, we showed recently that vaccines composed of autophagosomes (DRibbles) derived from syngeneic sarcomas could induce cross-reactive T-cell responses and cross-protection against the tumor. This unusual property of DRibbles was related to the selective recruitment of defective ribosomal products (DRiPs) and other short-lived proteins (SLiPs) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Inhibition of autophagy at this stage prevents breakdown of DRiPs and SLiPs that have concentrated in the autophagosome, and allows for fractionation and collection of the DRibble corpuscles to provide the protein needed to create effective DRibble vaccines 89 . DRibble tumor vaccines developed from these proteins have been shown to induce cross-reactive T-cell responses and tumor antigen cross- protection 90 . Preliminary analysis of a Phase II trial evaluating the use of DRibble vaccines in patients with non-small cell lung cancer (NSCLC) demonstrated that at 12 weeks, PBMCs from treated patients had multiple induced and increased antibody responses 91 .…”
Section: Targeting Autophagy: a Good Idea?mentioning
confidence: 99%
“…Inhibition of autophagy at this stage prevents breakdown of DRiPs and SLiPs that have concentrated in the autophagosome, and allows for fractionation and collection of the DRibble corpuscles to provide the protein needed to create effective DRibble vaccines 89 . DRibble tumor vaccines developed from these proteins have been shown to induce cross-reactive T-cell responses and tumor antigen cross- protection 90 . Preliminary analysis of a Phase II trial evaluating the use of DRibble vaccines in patients with non-small cell lung cancer (NSCLC) demonstrated that at 12 weeks, PBMCs from treated patients had multiple induced and increased antibody responses 91 .…”
Section: Targeting Autophagy: a Good Idea?mentioning
confidence: 99%
“…Vx3 protein was expressed and purified based on our previous work. 19,20 In brief, pUbiG101-Vx3(A7)-eGFP expressing plasmid was introduced into E. coli DH5-α competent cells (Invitrogen) to induce the expression of His-Vx3-eGFP fusion protein. Next, cells were harvested and treated with lysozyme (Sigma).…”
Section: Expression and Purification Of Vx3 Proteinmentioning
confidence: 99%
“…12 Recent studies have confirmed that DRibbles (defective ribosomal products-containing blebs) isolated from tumor cells with the induction of autophagy and inhibition of lysosomal/proteasomal activity are sufficient to stimulate dramatic T-cell activation and kill carcinoma cells in different tumor models such as melanoma, lung cancer, breast cancer and liver cancer. [13][14][15][16][17][18][19] Moreover, we have demonstrated that ubiquitinated proteins (UPs) are the critical TAA source of DRibbles which induce the antitumor efficacy. Therefore, different strategies for UPs enrichment have been developed to achieve a clinically safe, simply made, and environment-friendly vaccine with enhanced antitumor immune response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations